Biochemical and Microbial Quality Attributes of Cow’s Milk in Respect to Regional Discrimination in Bangladesh - , Mst. Afifa Khatun; , Biplob Kumar Roy; , Arzina Hossain; , Ashikur Rahman; , Md. Kamruzzaman Munshi; , Mahfuza Islam; , Md. Afzal Hossain; , Mohammad Ashraful Islam Bhuiya; , Md. Mazibur Rahman; , Roksana Huque (Archives of Current Research International, 2018)
Aims: The aim of this study was to assess inter-regional quality and safety of cow milk of Bangladesh. Study Design: Collection of raw cow's milk from different dairy farms, analysis of samples, and statistical analysis to find out the discrimination among the studied regions as quality and quantitative risk assessment. Place and Duration of Study: Three different regions (South-Central, North-Western and Western regions) of Bangladesh (August to December 2016). Methodology: Biochemical composition (protein, total fat, solids-non-fat, total casein, and lactose) was determined using the Lactostar auto milk analyzer. Different microbial status of collected cow's milk has been investigated by Standard Plate Count (SPC) method. Results: Significant differences were observed in the content of milk protein, fat, solids-non-fat, casein, and lactose among those regions. Milk from West region of Bangladesh contains significantly higher content of total protein (4.06%), casein protein (2.91%), solids-non-fat, and lactose compared to other regions. However, South-Central milk possesses a significantly higher level of fat (3.84%). The Pearson’s correlation indicated that the content of milk protein, casein, lactose and SNF are positively correlated (P=.05 and <0.01) with each other whereas milk fat was found to be negatively correlated with other constituents of milk. The Box plot and canonical discriminate analysis based on biochemical parameters revealed good distinction among individual geographic origin. A significant difference was shown in microbiological quality of raw milk from the three studied regions and South-Central region showed highest microbial contamination compared to North -Western and Western regions. Conclusion: The present study has strongly indicated regional variation in cow milk quality. Statistical analysis (Canonical Discriminate) of the milk constituents provides a prospect for geographic discrimination of raw milk and thus showed good regional separation among three studied regions of Bangladesh. The study would be useful to analyze more diverse dairy products in the future leading to more effective determination of geographic origin.